BUILDing pathways to health-related research careers in biomedical and behavioral sciences: a longitudinal evaluation of postbaccalaureate outcomes using a matched comparison group - Arruda, Erin H.; Vu, Kim-Phuong L.; Chun, Chi-Ah; Galvez, Gino; Marayong, Panadda; Dillon, Jesse G. (Frontiers in Education, 2025)
The BUilding Infrastructure Leading to Diversity (BUILD) undergraduate research training program is funded by the National Institutes of Health (NIH) to strengthen the pipeline for underrepresented students through graduate school and into health-related research careers in the biomedical and behavioral sciences. This study evaluates the impact of BUILD participation at a Minority-Serving Institution in Southern California on graduate school outcomes up to 6 years post-graduation including doctoral program enrollment and degree attainment using a quasi-experimental design. BUILD students were compared to a propensity score matched non-BUILD group using logistic regression. Results showed BUILD students enrolled in Ph.D. programs and attained Ph.Ds. at a higher rate compared to matched peers. Findings indicate BUILD met a pivotal program objective to increase doctoral degree attainment imperative for health-related research careers in biomedical and behavioral sciences. Furthermore, results support the added value of undergraduate research programs for students from underrepresented backgrounds.